Does cartographic education need an epistemology? Traditions and transitions in Brazilian school cartography - Jorn Seemann (Universidade Federal de Santa Catarina, 2022)
Knowledge philosophies have been a constant theme in cartography for the last three decades and have resulted in a lively debate on a variety of approaches (modern, postmodern post-processual and post-representational) in the field. These discussions have not had a significant impact on theories and methodologies in cartographic education. Teaching about and with maps embraces well-established ideas, but is reticent to accept alternative modes. This article seeks to analyze cartographic views and epistemologies in the context of school cartography in Brazil in order to point out traditions, transitions and trends that consolidate easy-to-follow principles, but may curb a diversity of approaches in the subfield at the same time. I argue that teaching with maps requires a broader debate about adjustments and innovations beyond the taken-for-granted standards. For this purpose, I will briefly discuss epistemologies in the context of scientific cartography and then, based on the existent substantial bibliography on cartographic education in Brazil, outline specific traditions that have laid the foundations for today's school cartography in the country. Obstacles and challenges for the development and improvement in teaching are identified, with the intention to rethink common practices and experiment alternative or complementary forms and modes in the classroom. The revision and reformulation of specific principles, concepts and themes can strengthen an inclusive, diversified and pluralistic vision in cartographic education that can serve as a useful tool for citizenship cartography in Brazil.